The Translation of the Qur’an into Bebaso: An Analysis of Its Implications for the Epistemology of Tarjamat Al-Qur’ān Studies - John Supriyanto; Abdullah Idi; M Syawaluddin; Pathur Rahman (An-Nida', 2026)
This article explores the epistemological implications of translation within the discipline of tarjamat al-Qur’ān, with particular emphasis on the objectives of translation, translation models, and the qualifications of translators. Utilising a qualitative approach with a mixed-methods design, the study integrates document analysis, participant observation, and in-depth interviews with translators, validators, and members of the Bebaso-speaking community. The findings indicate a shift in the orientation of Qur’anic translation from an originally educational-theological function towards an educational-cultural role, wherein the translation of the Qur’an serves as a tool for language documentation, identity reinforcement, and the symbolic legitimisation of local languages. In relation to translation models, the study identifies a hybrid and layered pattern of tarjamat al-Qur’ān that employs Indonesian as an intermediary language, necessitating a multi-tiered mechanism of meaning control through processes of verification, validation, and reference to authoritative exegetical sources. Regarding translator qualifications, the research reveals a transition from the paradigm of an individual mutarjim possessing comprehensive competence to a collaborative and multidisciplinary translation model that distributes scholarly authority among team members. These findings demonstrate that the epistemology of tarjamat al-Qur’ān is dynamic and responsive to socio-cultural contexts, while maintaining adherence to the normative principles of fidelity to meaning and theological caution in engaging with divine revelation.